Critical National Assets and Infrastructure and National Security Architecture In Nigeria: An Evaluation - Ukaeje, Obinna; Yoroms, Gani Joses (Journal of Central and Eastern European African Studies, 2026)
Critical national assets and infrastructure are essential for effective functioning of the state and well-being of the citizens, of which their disruption would have a devastating impact on the state. It is on this premise that the Nigerian government made CNAI a key component of its national security to be protected under the national security architecture. However, despite efforts of the government through the office of the national security advisor, whose responsibility is to coordinate the country’s national security architecture, CNAI Protection in Nigeria remains weak, thereby increasing the vulnerability of these infrastructure and national assets to vandalism and attack. Using qualitative research approach and dwelling largely on empirical literature and documented evidence, the paper examined the endangered state of CNAI in Nigeria and the efforts of the federal government toward safeguarding and protecting these vital assets. The paper found out that there is a serious gap between the policies and strategies of ONSA and the implementation itself, which it attributed to challenges like poor coordination, interagency rivalry, and sabotage among others. The paper therefore recommends among others the full implementation of CNAIP Protection Strategy as articulated in the NSS 2019, improve resource allocation for agencies responsible for CNAI Protection, and enhanced cooperation among agencies responsible for the protection of these critical assets.